Design of Project-Based Critical Thinking Skills Assessment Instrument for Class X High School Students on Climate Change Materials - Oria Lasmana; Festiyed Festiyed; Abdul Razak; Muhyiatul Fadilah (Eduvest - Journal of Universal Studies, 2024)
Critical thinking skills are one of the essential competencies that students in the 21st century must possess. Biology learning in high school emphasizes the development of critical thinking skills, which are essential abilities in understanding, analyzing, and evaluating complex information. This research aims to design a critical thinking skills assessment instrument based on Project-Based Learning for Class X High School Students on climate change material. This study uses a descriptive research method. The data collection technique in this study is by observation and literature study. The preparation of this assessment instrument is designed based on the Scientific Literacy Assessment (SLA). The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and drawing a conclusion. The results of the study show that a design of observation sheets and assessment instruments has been produced that can be used to measure students' critical thinking skills. This assessment instrument for students' critical thinking skills is designed based on SLAs and is ready to be validated so that a valid assessment instrument is produced. Teachers can use this assessment instrument to assess students' critical thinking skills in project-based learning. This instrument can also be used to provide constructive feedback to students and help them improve their critical thinking skills.